ANALISIS BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA CAFÉ DOIKU MARENDAL - Hayati , Fitri; Siregar, Dedy Rahman (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2025)
Organizational culture is increasingly becoming the focus of attention in the business world because there are many benefits that can be derived from organizational culture. Organizational culture forms an environment within a company that can stimulate creativity and motivation, which can improve work performance. A strong and good organizational culture can form high organizational performance and increase company productivity and effectiveness. Apart from that, job satisfaction is an important factor that can influence employee performance. Employers should pay attention to job satisfaction and work motivation to improve employee performance and the performance of the company or organization as a whole. Good employee performance can improve the quality and optimal performance of a company or organization. The research method used in this research is qualitative research using probability sampling techniques with a purposive sampling approach to take samples. Questionnaires will be distributed to Cafe Doiku customers. The sample size is 20 respondents. The result of this research is the influence of the organizational culture variable (X1) on the Employee Performance variable Y. From the analysis it was found that the significant value was (0.000 < 0.05), which means that the organizational culture variable has a significant influence on employee performance. The influence of the Job Satisfaction variable (X2) on the Employee Performance variable Y from the analysis shows that the significant value is (0.004 < 0.05), which means that the job satisfaction variable has a significant influence on employee performance.